Designing A Web-Based Reporting Application For Elementary School Kompleks Sambung Jawa - Asnimar; Akbar Iskandar; First Wanita; Kamaruddin; Erwin Gatot Amiruddin; Akbar Hendra; Mansyur; Oluwaseun Tobechukwu (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2024)
The management of student report cards at the Sambung Jawa Complex Elementary School still uses Microsoft Excel which can cause the data processing process to be less efficient and prone to errors. The aim of this research is to build a report card application that can increase the efficiency and accuracy of processing student report card data, as well as facilitate access and management of data by teachers and administrative staff. The method used in designing this application is the FAST method (Framework for the Application of Systems Thinking), which includes the stages of requirements analysis, system design, and implementation. Meanwhile, the testing method used is the black box method, which focuses on testing the functionality of each feature in the application without looking at its internal structure. The results of this research show that the designed web-based report card application can run well and fulfill the needs of report card management at the Sambung Jawa Complex Elementary School. This application has succeeded in increasing the efficiency and accuracy of processing report card data, as well as making data access and management easier by the school.